The skin I'm in - Flake, Sharon G. (Disney/Jump at the Sun, 2018)
Thirteen-year-old Maleeka Madison, insecure about her very dark skin, rejects the support of a new teacher, Miss Saunders, whose skin looks blotched because of a rare medical condition--but soon Maleeka begins to see that Miss Saunders could be a role model, and that she must learn to love herself and accept love from others.